Medical Co-Morbidities in COPD and Their Influence on Patient Well-Being: A Systematic Literature Review - Chandra, Amrish; Rawat, Geeta; Walia, Vaibhav (Journal of Neonatal Surgery, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a leading cause of morbidity and mortality globally. Understanding the burden of medical co-morbidities in COPD patients is crucial for improving patient care and outcomes. Objective: This study aims to systematically review and synthesize current literature on the impact of medical co-morbidities on the well-being of patients with COPD. Methodology: Employing the PRISMA guidelines, a comprehensive search was conducted across “PubMed, Web of Science, and Scopus databases”. From an initial pool of 925 articles, 57 were selected for detailed review. The analysis involved creating a thematic map, a word cloud. Findings: The SLR revealed COPD's complex interaction with co-morbidities. COPD's elderly and middle-aged patients' medical co-morbidities are a major problem. Hospitalization rates, quality of life, and death show how these co-morbid disorders affect patient outcomes. Conclusion: The study highlights the significant, yet evolving, burden of co-morbidities in COPD, emphasizing the complex interplay between aging, lifestyle factors, and disease progression. Implication: Findings underscore the need for holistic patient management strategies in COPD, considering the multifaceted impact of co-morbidities on patient well-being.